In situ Rb/Sr geochronology and stable isotope geochemistry evidence for Neoproterozoic and Paleozoic fracture-hosted fluid flow and microbial activity in Paleoproterozoic basement, SW Sweden. - Drake, Henrik (Linnaeus University, 2023)
Data tables presenting raw data and reduced data with isotopic, molecular and geochronology information. The isotopic data involves C, O, S, and Sr isotopes for unknowns and reference materials. The geochronology data involves Rb/Sr data for unknowns and reference materials. The samples are from Gothenburg, Sweden.

Raw and reduced data from analysis of C, O, S, Sr, Rb/Sr isotope systems in geological materials, along with organic geochemistry data. The tables include both data from unknowns and reference materials.

Data tables, isotopic, molecular and geochronology

Rådata och reducerade data från analyser inom isotopsystemen C, O, S, Sr och Rb/Sr, tillsammans med organisk geokemidata.
In situ Rb/Sr geochronology and stable isotope geochemistry evidence for Neoproterozoic and Paleozoic fracture-hosted fluid flow and microbial activity in Paleoproterozoic basement, SW Sweden.
Keywords: Stable isotopes; Stabila isotoper; microbiology; mikrobiologi; Natural Sciences; Naturvetenskap; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Geology; Geologi; Geochemistry; Geokemi; Microbiology; Mikrobiologi